2006
DOI: 10.1021/om058051y
|View full text |Cite
|
Sign up to set email alerts
|

Sila-venlafaxine, a Sila-Analogue of the Serotonin/Noradrenaline Reuptake Inhibitor Venlafaxine:  Synthesis, Crystal Structure Analysis, and Pharmacological Characterization

Abstract: The serotonin/noradrenaline reuptake inhibitor rac-1- [2-(dimethylamino)-1-(4-methoxyphenyl)ethyl]cyclohexan-1-ol (rac-venlafaxine, rac-1a) is in clinical use as an antidepressant. The silicon analogue, rac-1-[2-(dimethylamino)-1-(4-methoxyphenyl)ethyl]-1-silacyclohexan-1-ol (rac-sila-venlafaxine, rac-1b), was synthesized in multistep syntheses, starting from tetrachlorosilane or tetramethoxysilane. The corresponding 1-silacyclopentan-1-ol derivative rac-2 was prepared analogously. The sila-venlafaxine enantio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 30 publications
1
45
0
Order By: Relevance
“…In addition, crystallographic data (excluding structure factors) for the structures reported in this paper have been deposited with the Cambridge Crystallographic Data Centre as supplementary publication nos. CCDC-661268 (5) and CCDC-661269 (6). These data can be obtained free of charge from The Cambridge Crystallographic Data Centre via www.ccdc.cam.ac.uk/data_reques-et.cif.…”
Section: Identification Of the Major In Vitro Metabolites Of Sila-halmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, crystallographic data (excluding structure factors) for the structures reported in this paper have been deposited with the Cambridge Crystallographic Data Centre as supplementary publication nos. CCDC-661268 (5) and CCDC-661269 (6). These data can be obtained free of charge from The Cambridge Crystallographic Data Centre via www.ccdc.cam.ac.uk/data_reques-et.cif.…”
Section: Identification Of the Major In Vitro Metabolites Of Sila-halmentioning
confidence: 99%
“…[3] With these considerations in mind, we examined the biological effects of sila-substitution (C/Si exchange) [4] of haloperidol (1 a) and thus synthesized its silicon analogue, sila-haloperidol (1 b), [5] whereby the R 3 COH carbon atom in the piperidine ring was replaced by a silicon atom. In context with our systematic research on silicon-based drugs, [6] we carried out a full characterization of 1 b·HCl (solution NMR studies, crystal structure analysis, ESI-MS studies of aqueous solutions) complemented by radioligand binding studies on hD 1 , hD 2 , hD 4 , and hD 5 human dopamine receptors at that time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2,3] It has been shown to act as an allosteric modulator of the GnRH receptor [4] and is highly efficacious in in vivo models of hormone suppression. Replacement of a carbon atom with a silicon atom (sila-substitution) is a novel tool for drug design [5,6] that has already been used in the design of GnRH antagonists. It has been demonstrated that the carefully targeted introduction of silicon into a GnRH antagonist, in this case a peptide, can lead to enhanced bioactivity as a result of improved pharmacokinetics.…”
Section: Introductionmentioning
confidence: 99%
“…Venlafaxine and its silicon analog silavenlafaxine displayed similar physicochemical properties but different pharmacological selectivity profiles (Daiss et al, 2006). Fexofenadine is a histaminic H 1 receptor antagonist used in the treatment of allergies.…”
mentioning
confidence: 99%